Elementary PE Teachers Perception on The Implementation of Online Learning During Covid 19 Pandemic in West Nias 2021 - Ibrahim Sembiring; Bayu Insanistiyo; Mariyance Prida Mehaga (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine how positive the perception of PE teachers are on the implementation of online learning during Covid-19 Pandemic in West Nias in 2021. This research is quantitative descriptive study with survey method. Data has been collected using questionnaire instrument and analyzed using descriptive statistics with percentages. Population in this study amounted to 106 elementary PE teachers in West Nias using Quota Sampling technique to determine number of samples used. With reliability score of 0.975, this study is declared reliable. Based on the overall results, it was concluded that 8% of the sample said that online learning was very positive, 26% said it was positive, 24% said it was somewhat positive, 42% said it was negative, and 0% said it was very negative. This result means that most of the teachers thought that online learning gave negative impact.